Peran Indonesia Dalam media Konflik Kamboja - Thailand - Anditya Restu Aji (Jurnal Studi Diplomasi dan Keamanan, 2015)
Shooting incident on Preah Vihear Temple on February 2011 between Thailand and Cambodia military forces marked the fragility of ASEAN stability. It has been widely acknowledged that ASEAN member states has conflicting issues each other, commonly related to territorial boundaries. For Indonesia, which became ASEAN chairman in 2011, the conflict was a moment of testing Indonesia’s leadership in ASEAN. This article aims at describing Indonesia’s effort to mediate Thailand and Cambodia Conflict. Since ASEAN maintains its position not to involve in domestic affairs of every member. Based on Treaty of Amity and Cooperation and ASEAN Charter, Indonesia conducted shuttle diplomacy and facilitated many informal meeting to resolve the conflict. This case proofed that ASEAN way once again works in restraining violence conflict, although it did not address the root of the problem.